W. SHAKESPEARE’S “HAMLET” IN CONTEXT OF E. LEVINAS’S PHILOSOPHICAL CONCEPT OF MAN: DISCOVERING ‘THE OTHER’ AS A MEANINGFUL SUBTEXT OF THE TRAGEDY - Natalia I. Astrakhan (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The article concentrates on the study of the relationship between literary-artistic and philosophical discourses in the process of verbalizing universal cultural meanings of existence and building a holistic concept of man as an uppermost task of creation and re-creation (interpretation) of a literary work through the example of W. Shakespeare’s tragedy “Hamlet”. The article aims to interpret W. Shakespeare’s tragedy “Hamlet” in the context of ideas of the French thinker E. Levinas, one of the founders of the philosophy of dialogue. The tasks of the study are to characterize the significance of the dialogical vision of personality for the contemporary interpretation of the classics of world literature, to reveal the importance of dialogue between artistic and philosophical discourses while cognizing the human being in his interaction with the world and to consider the system of images in W. Shakespeare’s tragedy “Hamlet” with regard to the philosophy of the Other, developed in E. Levinas’s works “Time and the Other” and “Humanism of the Other”. The main research methods include culture-historical and hermeneutic methods applied in addition to the fundamental ideas of the philosophy of dialogue. The article deals with the tragedy “Hamlet” by W. Shakespeare as a prototext for E. Levinas’s philosophical work “Time and the Other”. Shakespearean reminiscences are characterized as important in terms of the development of the Levinasian concept of man. According to Levinas, the essence of the person is revealed in the dialogical interaction with the Other, which allows one to go beyond the present as captivity, discover the connections with the future in which the subject no longer exists, and achieve the eventful fullness of being, which leads to harmony and opens the way to the transcendental subject and eternity. The system of images in W. Shakespeare’s tragedy “Hamlet” allows one to associate the title character with different variants of the Other, which become significant for him as he fulfils the Ghost’s will. The unfolding of the action can be interpreted as such that it features the establishment of dialogical interaction between the father and the son in its meaningful subtext. At the level of events, the achieved interaction is seen as the fullness of the characters’ personal existence (above all, that of Hamlet and the Ghost), which manifests itself in overcoming the boundary between life and death, restoring the normal course of history and asserting the necessity for the superiority of good over evil. Horatio, the actor (i.e. the First Player), and jester Yorick (an offstage character in the prince’s memories), each of whom represents the conditions necessary for genuine dialogical interaction (belonging to a tradition, empathy, carnival freedom and, therefore, the familiarity of contact with another person), become significant variants of the Other to Hamlet, metonymically equivalent to his father the king.